Youth sport specialization associated with poorer lower extremity function & pain as young adults - Dobscha, M.; Peterson, C.; Powers, W. S.; Goetschius, J. (The Physician and Sportsmedicine, 2023)
Objective Examine the link between youth sports specialization and long-term lower extremity joint health after sports by comparing lower extremity function, pain, and history of sport-related injuries between young adults that were highly, moderately, and low specialized in youth sports.